The Legal Position of the Credit Agreement on the Mortgage Object in the Status of the Sale and Purchase Agreement - Jernidar Zebua; Bambang Tri Bawono (Sultan Agung Notary Law Review, 2022)
This research aims to find out and analyze the legal position of the credit agreement on the object of collateral for land rights that are still in the status of a binding sale and purchase agreement in full with the Bank. The type of research is empirical normative and research specifications are descriptive analytical research. The data required prioritizes secondary data through document study methods or library materials and primary data as support through interviews. Methods of data analysis using the methodqualitative analysis. Based on the research, it was concluded that the legal position of the credit agreement on the object of collateral for land rights which is still in the status of a binding sale and purchase agreement in full is a credit agreementwho have met the subjective requirements and objective requirements based on article 1320 of the Civil Code and article 38 of the UUJN for notarized credit agreements that are in the principal agreement binding on the parties and the Debtor is subject to carrying out his achievements based on the agreement contained in the credit agreement. The guarantee agreement that was preceded by SKMHT and the drafting of which was contrary to UUHT is invalid or null and void and cannot be used as a basis for granting mortgage rights and registration at the land office and the Bank is domiciled as a concurrent creditor. The principal agreement does not terminate over an invalid guarantee agreement. Conversely, if the main agreement is canceled then the follow-up agreement (accessoir) become void or terminate automatically. Debtors who heed the implementation of the contents of the credit agreement can take a persuasive approach (non-litigation) or attempt a default lawsuit (litigation) in court based on a mutually agreed credit agreement at the beginning of the credit.